From Inactivity to Work The Role of Active Labour Market Policies - Carcillo, Stéphane (OECD Social, Employment and Migration Working Papers, 2006)
Many OECD countries have in recent decades experienced periods of relatively rapid growth in nonemployment benefit expenditures and recipiency rates which have not subsequently been reversed. By contrast, in a number of OECD countries the number of unemployment benefit recipients has declined fairly sharply since the mid-1990s. Although national situations for particular benefits vary greatly, a variety of evidence suggests that there is now often substantial scope for bringing people currently in the sick and disabled, lone-parent, old-age and non-categorical social assistance groups into employment